2001
DOI: 10.1088/0952-4746/21/3/303
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic radiation from microwave ovens

Abstract: Electromagnetic radiation from microwave ovens in Saudi Arabia was investigated by means of a field measurement survey. The survey was carried out for 106 ovens used in households and restaurants in Riyadh city. Ovens were between 1 month and 14 years old with operating power ranging from 0.5 to 4.4 kW. One oven was found to leak more than the 5 mW cm(-2) limit specified in the standard. Fifteen other ovens were found to leak 1 mW cm(-2) or more, with the remaining ovens leaking less than that. Based on the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The ability to control these interactions primarily decides quality of the drilled hole. At the same time, Alhekail (2001) emphasized on ensuring that the interactions are performed in an enclosed atmosphere (applicator). While considering microwave material interaction, there are basically three different types of materials -transparent, absorptive and reflective.…”
Section: Symbols Dmentioning
confidence: 99%
“…The ability to control these interactions primarily decides quality of the drilled hole. At the same time, Alhekail (2001) emphasized on ensuring that the interactions are performed in an enclosed atmosphere (applicator). While considering microwave material interaction, there are basically three different types of materials -transparent, absorptive and reflective.…”
Section: Symbols Dmentioning
confidence: 99%
“…These studies show that microwave leakage mostly satisfies the IEC norm of 5 mW cm 22 . Alhekail (9) investigated 106 domestic and restaurant microwave ovens and showed that only one oven exceeded the IEC norm, 15 other microwave ovens had leakage levels of 1 mW cm 22 or more. Bangay and Zombolas (10) mention that only 0.8 % of microwave ovens (Australia) have leakage in excess of the IEC limit.…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitous availability of these appliances has provided people with unprecedented convenience. However, these modern conveniences may have exposed the consumers to some possible negative influences [1][2][3]. According to some recent studies, electromagnetic radiation produced by various high-tech office equipment and household appliances has become another source of indoor environment pollutions in addition to air pollution, radioactive pollution and noise pollution.…”
Section: Introductionmentioning
confidence: 99%